Isoniazid Induced Psychosis - Sharad Chand (Journal of Global Pharma Technology, 2019)
Isoniazid (INH) is one of the primary drugs used in the treatment of Mycobacterium tuberculosis infection. The common side effects of INH are peripheral neuropathy, hepatitis, rashes. Rarely psychosis, convulsions, and even death have been reported on regular doses of this drug. We present a case of Isoniazid induced psychosis occurring in a 36-year-old female patient was admitted to the general medicine unit for tuberculosis. The case was analyzed for suspected ADR and found to be probable ADR of isoniazid. The drug was discontinued, and antitubercular therapy was changed to modified approach,i.e. (R- Rifampicin 450mg, I- Ethambutol 800mg, S-Streptomycin 750mg and O- Ofloxacin 400mg) which shows clinical improvement in the patient.